The tactical and organizational basis of processing of some cover investigative (search) actions at the initial stage of investigation of home invasion robbery - Шульга , Ю. О. (Київський національний університет імені Тараса Шевченка, ТОВ «Правова Єдність», 2017)
The problem issues of the tactical and organizational principles of conducting cover investigative (search) actions at the initial stage of investigation of home invasion robberies were analyzed in the article, in accordance with the norms of the Criminal Procedural Code of Ukraine, other normative legal acts, data of investigative and judicial practice and scientific sources, The article contains some suggestions of the necessity of qualitative the organizational and tactical support for the conduct of cover investigative (search) actions. The effectiveness of the initial stage of the investigation of robberies committed with housing penetration depends to a large extent on the organization and tactics of the investigation. The effectiveness of the initial stage of the investigation of robbery committed with the penetration to house, largely depends on the organization and tactics of the investigation. The investigator is responsible for the organization and tactics of the investigation, additionaly, investigator is responsible for the reasonableness of the tactical decisions, wich were taken, since the criminal procedure of robberies was started. The specificity of the conduction of cover investigative operations is determined by the severity of this type of crime. The peculiarities of robberies and the specific conditions of their conduction are penetration into the home. In addition to, the article contains the issue of the decision to conduct cover investigative (search) actions. According to the Criminal Procedural Code of Ukraine such decision is taken by the investigating judge upon the request of the prosecutor or at the request of the investigator, agreed with the prosecutor, is discussed and argued.

Відповідно до норм Кримінального процесуального кодексу України, інших нормативно-правових актів, даних слідчої та судової практики, а також наукових джерел у статті проаналізовано проблемні питання тактико-організаційних засад провадження окремих негласних слідчих (розшукових) дій на початковому етапі розслідування розбоїв, вчинених із проникненням у житло, внесено пропозиції щодо їх вирішення та обґрунтовано необхідність якісного організаційно-тактичного забезпечення провадження окремих негласних слідчих (розшукових) дій.
ТАКТИКО-ОРГАНІЗАЦІЙНІ ЗАСАДИ ПРОВАДЖЕННЯ ОКРЕМИХ НЕГЛАСНИХ СЛІДЧИХ (РОЗШУКОВИХ) ДІЙ НА ПОЧАТКОВОМУ ЕТАПІ РОЗСЛІДУВАННЯ РОЗБОЇВ, ВЧИНЕНИХ ІЗ ПРОНИКНЕННЯМ У ЖИТЛО
Keywords: organizational and tactical principles; cover investigative (search) actions; initial stage of investigation; robbery; penetration into the home; home invasion robbery; investigative situations.; організаційно-тактичні засади; негласні слідчі (розшукові) дії; початковий етап розслідування; розбої; проникнення у житло; слідчі ситуації.